2016
DOI: 10.3390/ijms17081314
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is characterized by renal dysfunction that is present for more than 3 months; it is also associated with a number of comorbidities [1,2].[...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…1 CKD is characterized by the progressive loss of kidney function over time. 2 In addition, the main causes of CKD are hypertension, diabetes, chronic pyelonephritis, and glomerular diseases (glomerulosclerosis and IgA nephropathy, diabetic nephropathy and lupus nephritis). [3][4][5] Evidence has shown that patients with diabetes or hypertension should be screened on an annual basis for CKD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 CKD is characterized by the progressive loss of kidney function over time. 2 In addition, the main causes of CKD are hypertension, diabetes, chronic pyelonephritis, and glomerular diseases (glomerulosclerosis and IgA nephropathy, diabetic nephropathy and lupus nephritis). [3][4][5] Evidence has shown that patients with diabetes or hypertension should be screened on an annual basis for CKD.…”
Section: Introductionmentioning
confidence: 99%
“… 7 The stages of CKD range from mild loss of kidney function in stage 1 (eGFR > 90 mL/min/1.73 m 2 ) to complete kidney failure in stage 5 (eGFR < 15 mL/min/1.73 m 2 ). 2 , 8 Stage 5 of CKD is known as end-stage renal disease (ESRD), and patients with ESRD require dialysis or a kidney transplant to stay alive. 7 , 9 Because CKD can progress to kidney failure (also called ESRD) and even death, early diagnosis of this disease is important for timely preventive and therapeutic interventions and preventing a time-dependent decline in eGFR.…”
Section: Introductionmentioning
confidence: 99%
“…This is an unexpected finding, as many studies suggested that cancer risk would be increased in the CKD patients. [ 7 12 , 21 31 ] The further surprising finding was that our study showed a negative association between CKD and GC.…”
Section: Discussionmentioning
confidence: 53%
“…[ 6 11 ] CKD is defined as kidney damage or decreased kidney function [glomerular filtration rate (GFR) lower than 60 mL/min per 1.73 m 2 ] for 3 months or longer. [ 12 14 ] The prevalence and incidence of CKD is significantly increasing in decades. [ 15 17 ] Compared with other countries, Taiwan has a remarkably high incidence and prevalence of patients with CKD, and end-stage of renal disease (ESRD).…”
Section: Introductionmentioning
confidence: 99%
“…It has the advantages of low cost, a simple procedure and allowing patients to perform self‐assisted dialysis at home. In addition, it has good residual renal function protection and a small impact on the body's internal environment and is being used as the preferred treatment method by increasingly more patients (Parrish, ). Currently, it is estimated that more than 272,000 patients receive PD treatment worldwide, accounting for approximately 11% of the global dialysis population (Li et al., ).…”
Section: Introductionmentioning
confidence: 99%